Record of Microspodian Parasitisation of Dung Beetles (Coleoptera:Scarabidae) in a Natural Scrub Ecosystem of Tamil Nadu - A, Anitha Rani.; Sanjayan, K. P. (Asian Journal of Biological and Life Sciences, 2013)
The two year survey of microsporidia parasitizing dung beetles in a natural scrub jungle ecosystem of Tamil Nadu indicated twelve of the thirty three species of dung beetles to be infected with Nosema sp. whereas five species were found to be infected with Vairimorpha sp and mixed infection was observed in three species of Onthophagus beetles. The percentage of infection is very low in Copris excisus (2.5%) and high in Euoniticelles fulvus 6(63.75%), the spore yield was high in Oniticellus cinctus (3.4 x10 6) among the dung beetle populations of the scrub jungle. Being essentially nature's scavengers, the role of microsporidians in limiting the ecological services of the dung beetles is discussed.